1949
DOI: 10.1017/s0021859600004639
|View full text |Cite
|
Sign up to set email alerts
|

Placement of fertilizers for row crops

Abstract: Fertilizer placed in contact with the seed damaged the germination of sugar beet, mangolds, swedes and peas in 1947; damage was also caused by fertilizer placed directly below the seed. In 1947 and 1948 some damage to the germination of sugar beet was caused by fertilizer in bands 3 in. below the soil surface and 1 in. to the side of the seed; in both years bands of fertilizer 3 in. to the side of the seed were safe. Where placement of medium or full fertilizer dressings is adopted for row crops, the bands sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1954
1954
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…A specially constructed three-row placement drill (described by Cooke, 1949) was used in previous experiments on row crops. This machine was used The one-row machine is illustrated in Text- fig.…”
Section: Machinery For the Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…A specially constructed three-row placement drill (described by Cooke, 1949) was used in previous experiments on row crops. This machine was used The one-row machine is illustrated in Text- fig.…”
Section: Machinery For the Experimentsmentioning
confidence: 99%
“…to the side of the seed. (Cooke (1949) showed that bands of fertilizer should be placed at least 2 in. to the side of the seed to avoid damage to germination.…”
Section: Scope Of the Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first trials the fertilizer was mixed with the seed. Actual fertilizer placement trials were conducted by Cooke (1949Cooke ( , 1951, in England as early as in the late 19405, and by Ludecke, Scheffer and Tiedemann (1956) in Germany in the early 19505. Although the results indicated that placement of fertilizer brought about some increase in yield, it has not generally been recommended; instead, it has been considered, e.g.…”
Section: Introductionmentioning
confidence: 99%